A match-day analysis of the movement profiles of substitutes from a professional soccer club before and after pitch-entry - Hills, Samuel P.; Barrett, Steve; Feltbower, Richard G.; Barwood, Martin J.; Radcliffe, Jon N.; Cooke, Carlton B.; Kilduff, Liam P.; Cook, Christian J.; Russell, Mark (PloS one, 2019)
Whilst the movement demands of players completing a whole soccer match have been well-documented, comparable information relating to substitutes is sparse. Therefore, this study profiled the match-day physical activities performed by soccer substitutes, focusing separately on the pre and post pitch-entry periods. Seventeen English Championship soccer players were monitored using 10 Hz Micromechanical Electrical Systems (MEMS) devices during 13 matches in which they participated as substitutes (35 observations). Twenty physical variables were examined and data were organised by bouts of warm-up activity (pre pitch-entry), and five min epochs of match-play (post pitch-entry). Linear mixed modelling assessed the influence of time (i.e., 'bout' and 'epoch'), playing position, and match scoreline. Substitutes performed 3±1 rewarm-up bouts∙player-1∙match-1. Compared to the initial warm-up, each rewarm-up was shorter (-19.7 to -22.9 min) and elicited less distance (-606 to -741 m), whilst relative total distances were higher (+26 to +69 m∙min-1). Relative total (+13.4 m∙min-1) and high-speed (+0.4 m∙min-1) distances covered during rewarm-ups increased (p <0.001) with proximity to pitch-entry. Players covered more (+3.2 m; p = 0.047) high-speed distance per rewarm-up when the assessed team was losing compared with when winning at the time of pitch-entry. For 10 out of 20 variables measured after pitch-entry, values reduced from 0-5 min thereafter, and substitutes covered greater (p ˂0.05) total (+67 to +93 m) and high-speed (+14 to +33 m) distances during the first five min of match-play versus all subsequent epochs. Midfielders covered more distance (+41 m) per five min epoch than both attackers (p ˂0.001) and defenders (p = 0.016). Acknowledging the limitations of a solely movement data approach and the potential influence of other match-specific factors, such findings provide novel insights into the match-day demands faced by substitute soccer players. Future research opportunities exist to better understand the match-day practices of this population.